Adaptation and validation of the hyper-independence scale among Indonesian university students using the Rasch model - Vera Yolanda Gustin; Desi Nurwidawati; Nisrina Nurika Agustin (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
This study aims to adapt and validate the hyper-independence scale among Indonesian university students. The adaptation process followed the guidelines of the International Test Commission, which included forward translation, expert review, and pilot testing. Data were collected from 200 university students across various study programs. Psychometric evaluation was conducted using the Rasch model to examine reliability, unidimensionality, and item functioning. The results demonstrated high reliability at both the person (0.93) and item (0.96) levels, supported by strong separation indices, satisfactory item fit. In the Rasch model, item fit statistics provide evidence of construct validity, as misfitting items indicate response patterns inconsistent with the expected measurement structure. Most items fell within the acceptable MNSQ range (0.7–1.3), with minor deviations that remained tolerable and did not compromise overall validity. The findings suggest that a proportion of students exhibit moderate to high levels of hyper-independence, which may hinder help-seeking behavior, reduce academic engagement, and contribute to mental health risks. Within Indonesia’s collectivistic cultural context, these tendencies may reflect shifting attitudes toward autonomy in higher education. Overall, the validated instrument can be used to identify hyper-independence tendencies in university settings and supports the development of educational interventions that balance independence with adaptive support utilization.